I am reading Optics by Eugene Hecht, and I am confused about the author's derivation of the differential wave equation:

To relate the space and time dependencies of $\psi(x, t)$, take the partial derivative of $\psi(x, t) = f(x')$ with respect to $x$, holding $t$ constant. Using $x' = x \mp vt$, and inasmuch as

$$\dfrac{\partial{\psi}}{\partial{x}} = \dfrac{\partial{f}}{\partial{x}}$$

$$\dfrac{\partial{\psi}}{\partial{x}} = \dfrac{\partial{f}}{\partial{x'}} \dfrac{\partial{x'}}{\partial{x}} = \dfrac{\partial{f}}{\partial{x'}} \tag{2.8}$$

because $$\dfrac{\partial{x'}}{\partial{x}} = \dfrac{\partial{x \mp vt}}{\partial{x}} = 1$$

Holding $x$ constant, the partial derivative with respect to time is

$\dfrac{\partial{\psi}}{\partial{t}} = \dfrac{\partial{f}}{\partial{x'}} \dfrac{\partial{x'}}{\partial{t}} = \dfrac{\partial{f}}{\partial{x'}} (\mp v) = \mp v \dfrac{\partial{f}}{\partial{x'}} \tag{2.9}$

Combining Eqs. (2.8) and (2.9) yields

$$\dfrac{\partial{\psi}}{\partial{t}} = \mp v \dfrac{\partial{\psi}}{\partial{x}}$$

This says that the rate of change of $\psi$ with $t$ and with $x$ are equal, to within a multiplicative constant, as shown in Fig. 2.5. The second partial derivatives of Eqs. (2.8) and (2.9) are

$$\dfrac{\partial^2{\psi}}{\partial{x}^2} = \dfrac{\partial^2{f}}{\partial{x'}^2} \tag{2.10}$$

and $$\dfrac{\partial^2{\psi}}{\partial{t}^2} = \dfrac{\partial}{\partial{t}} \left( \mp v \dfrac{\partial{f}}{\partial{x'}} \right) = \mp v \dfrac{\partial}{\partial{x'}} \left( \dfrac{\partial{f}}{\partial{t}} \right)$$

Since $$\dfrac{\partial{\psi}}{\partial{t}} = \dfrac{\partial{f}}{\partial{t}}$$

$$\dfrac{\partial^2{\psi}}{\partial{t}^2} = \mp \dfrac{\partial}{\partial{x'}} \left( \dfrac{\partial{\psi}}{\partial{t}} \right)$$

It follows, using Eqn. (2.9), that $$\dfrac{\partial^2{\psi}}{\partial{t}^2} = v^2 \dfrac{\partial^2{f}}{\partial{x'}^2}$$

I don't see how

$$\dfrac{\partial{\psi}}{\partial{t}} = \dfrac{\partial{f}}{\partial{t}} \tag{1}$$

We actually found that $\dfrac{\partial{\psi}}{\partial{t}} = \mp v \dfrac{\partial{\psi}}{\partial{x}}$, so I have no idea where the author got $\dfrac{\partial{\psi}}{\partial{t}} = \dfrac{\partial{f}}{\partial{t}}$ from?

I would greatly appreciate it if people could please take the time to clarify this.

  • $\begingroup$ $$\dfrac{\partial{\psi}}{\partial{t}} = \dfrac{\partial{\psi}}{\partial{x}}\dfrac{\partial{x}}{\partial{t}}+\dfrac{\partial{\psi}}{\partial{t}}\dfrac{\partial{t}}{\partial{t}} = \dfrac{\partial{f}}{\partial{t}}$$ but $$\dfrac{\partial{x}}{\partial{t}}=0$$ $\endgroup$ – Nosrati Sep 20 '18 at 14:52

$$ \psi(x, t) = f(\bar{x}) \to \frac{\partial}{\partial t}\psi(x, t) = \frac{\partial}{\partial t}f(\bar{x}) $$ this is true. The fact that $\frac{\partial}{\partial t}f(\bar{x})$ also equals something else is secondary.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.